001 In vivo electrocardiograms in a murine model of Brugada syndrome show ST elevation, atrioventricular block and increased QTC dispersion. (22nd September 2015) - Martin, C A; Zhang, Y; Grace, A A; L-H Huang, C
Abstract : Introduction: Studies of Brugada Syndrome (BrS) are often limited by the use of pharmacologically modified cellular or tissue preparations. We show that an in vivo murine genetic Scn5a +/− model reproduces the clinical electrocardiographic phenotype, thereby offering more direct modelling of BrS. We then use this model to investigate conduction and repolarization abnormalities associated with this condition. Methods: ECGs were obtained from anaesthetised WT and Scn5a +/– mice, before and after administration of flecainide or quinidine. Traces were examined for ventricular arrhythmias, atrioventricular (AV) block and ST elevation. RR, PR, QR and QTc intervals were measured, and dispersions in QRS and QTc calculated from differences between right precordial and limb leads. Results: Scn5a+/ − hearts showed ventricular arrhythmias, ST elevation and AV block. All these features were accentuated by flecainide, with mean ST elevation significantly increased from 0.17±0.03 mV to 0.40±0.07 mV (Abstract 001 Figure 1 ). Although quinidine did not exert ventricular arrhythmic effects in Scn5a +/− hearts, it had variable effects on ST segments and caused significant conduction abnormalities, which may limited its clinical usefulness in the management of BrS. Scn5a +/− hearts showed slightly increased ECG intervals compared to WT but none of these differences reached statistical significance. However, both flecainide and quinidine increased intervals in WT and Scn5a +/− mice, in contrast with discordant effects upon action potential duration found in previous studies. There was increased dispersion in QRS and QTc intervals for Scn5a+/− hearts compared to WT. In the Scn5a+/− hearts, flecainide increased dispersion in both QRS and QTc, whilst quinidine did not increase the dispersion in either (1.50±0.30 ms before drug for QTc to 3.43±0.30 ms with flecainide (p=0.01), and to 1.32±0.38 ms with quinidine (p=0.03) (n=5)) (Abstract 001 Figure 2 ). These changes directly parallel the respective pro- and anti- arrhythmic effects of flecainide and quinidine experimentally and clinically in BrS. Conclusions: We have demonstrated for the first time that a murine genetic BrS model reproduces the human electrocardiographic features, suggesting both conduction and repolarization abnormalities. We also show that whilst the QT interval is not a direct correlate of action potential duration in a specific cardiac region, QT dispersion may offer an indicator of increased transmural repolarization gradients and may be useful in risk stratification of BrS patients.